0
$\begingroup$

I was reading a book on discrete mathematics where they asked for a proof of "Show that for all real numbers $a$ and $b$ with $a > 1$ and $b > 1$, if $f(x)$ is $O(\log_b (x))$, then $f(x)$ is $O(\log_a (x))$". I searched Google where I found this,

$$\log_b(x) = \frac{\ln(x)}{\ln(b)}$$ $$\log_a(x) = \frac{\ln(x)}{\ln(a)}$$ $$\log_b(x) = \log_a(x)\cdot \frac{\ln(a)}{\ln(b)} = \log_a(x) \cdot \text{constant}$$

But I couldn't find the meaning of the last line. Is there another way to prove it?

$\endgroup$
1
$\begingroup$

The last line is simply the application of the first two: $$\log_b(x) = \frac{\ln(x)}{\ln(b)}= \ln(x) \cdot \frac{1}{\ln(b)} = \frac{\ln(x)}{\ln(a)} \cdot \ln(a) \cdot \frac{1}{\ln(b)} = \frac{\ln(x)}{\ln(a)} \cdot \frac{\ln(a) }{\ln(b)} = \log_a(x) \cdot \frac{\ln(a) }{\ln(b)}$$

Since $a$ and $b$ are constants, $\frac{\ln(a) }{\ln(b)}$ is constant as well.

$\endgroup$
1
$\begingroup$

You can prove it without resorting to natural logarithms as follows.

Let $y = \log_b(x)$

Then, by definition of the logarithm, $$b^y=x$$ and taking $\log_a$ of both sides gives $$\log_ab^y=log_ax\implies y\log_ab = log_ax\implies y=\frac{\log_ax}{\log_ab}\implies \log_bx=\frac{\log_ax}{\log_ab}$$

Finally, since $\frac{1}{\log_ab}$ is a constant, $\log_bx = k\log_ax$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.